Novel stable bucket elevator - WU MING; JIA YE; WANG BAIBING; BAO DEGANG; WANG GUANGWEN; WANG LIJIE; WANG SONG; KANG PENG (2022)
The utility model relates to the technical field of conveying, in particular to a novel stable bucket elevator. A novel stable bucket elevator comprises a machine head and a machine tail, an ascending machine barrel and a descending machine barrel which are composed of standard machine barrels and correspond to each other are arranged between the machine head and the machine tail, and a winnowing pan belt and a winnowing pan which are in circulating reciprocating are arranged in the ascending machine barrel and the descending machine barrel. An integral communicating joint for communicating the ascending machine barrel with the descending machine barrel is arranged at the joint of the standard machine barrels; the ascending machine barrel and the descending machine barrel are communicated through the integral type communication joint, the pressure difference of the pipe walls on the two sides is balanced, the structural strength of the pipe walls of the elevator is enhanced, the elevator runs more stably, a w